Engaging Indigenous Knowledges: From Sovereign to Relational Knowers - Brigg, Morgan (The Australian Journal of Indigenous Education, 2016)
Increasing engagement with Indigenous knowledges (IKs) in mainstream tertiary educational institutions presents both ethico-political and epistemological challenges. This article engages these challenges by first cautioning against making wholesale distinctions between IKs and Western knowledges (WKs) and then examining the epistemological and politico-cultural entailments of the figure of the mainstream WK knower. Although the WK knower is typically cast as a sovereign being in command of knowledge, the practicalities of processes of knowing reveal the knower as at least partially relational. While the sovereign knower typically returns to his/her self in mainstream WKs, thereby disavowing or subsuming cultural others in ways that compromise serious engagement with IKs, relationality suggests more positive possibilities for becoming susceptible to Indigenous concerns and ways of knowing. This does not spell a relativist agenda. Rather, it shows that knowledge is established through relational processes and that WK knowers might better engage IKs by become less sovereign and more relational knowers.